Footprints of large theropod dinosaurs and implications on the age of Triassic biotas from Southern Brazil - SILVA, Rafael Costa da (2012)
Dinosaur footprints found in an outcrop of the Caturrita Formation (Rio Grande do Sul State, Southern Brazil), associated with a diverse and well preserved record of fauna and ﬂora, reopen the debate about|its exclusive Triassic age. The studied footprints were identiﬁed as Eubrontes isp. and are interpreted as having been produced by large theropod dinosaurs. The morphological characteristics and dimensions of the footprints are more derived than those commonly found in the CarnianeNorian, and are more consistent with those found during the RhaetianeJurassic. The trackmaker does not correspond to any type of dinosaur yet known from Triassic rocks of Brazil. Recent studies with the paleoﬂoristic content of this unit also support a more advanced Rhaetian or even Jurassic age for this unit